Global sensitivity analysis for offshore wind cost modelling. Issue 9 (29th January 2021) - Borràs Mora, Esteve; Spelling, James; van der Weijde, Adriaan H.
Abstract: The costs of offshore wind are decreasing rapidly. However, there is a need to better understand the key drivers behind these cost reductions. New environmental regulations, economic policies, technological advancements and financing structures have resulted in a set of relationships that need to be considered in order to define risks and profitability for the next generation of offshore wind farms. We use an industry‐leading offshore wind cost modelling tool which integrates site characteristics, technology specificities and financial modelling expertise and apply state‐of‐art global sensitivity analysis methods for different classes of offshore wind farms, ranking the contribution of around 150 input parameters that influence the cost of offshore wind development. We show that the top 5 parameters when building an offshore wind investment business case are the wind speed, target equity rate of return, turbine costs, drilling costs and debt service coverage ratio. The contribution of this paper can help guide additional efforts towards reducing the uncertainty of those key parameters to decrease costs and provide a framework to choose global sensitivity analysis techniques for offshore wind techno‐economic models.